The effect of language prompts and game sports activities on strengthening students' psychological state - Jingyi Xie; Siyu Ma , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This research intends to examine the effect of language signals and game sports activities on the psychological reinforcement of pupils. The education research uses a combination of functional training, linguistic prompt, and sports games. This study used the Mental Health Diagnostic Test (MHT), SPSS statistics, and a sample of 400 college students to determine the results. After the trial, the subjects in the game group demonstrated significantly less anxiety, an inclination toward loneliness, and a tendency toward phobia (p<0.05) compared to those before the experiment. More than 79.65 percent of the 172 boys have a medium or high level of activity, indicating that boys are active and motivated to engage in physical exercise. Among the 228 female students, 156 were inactive, accounting for 68.42%; just 5.26 % of female students have a high activity level, indicating that female students lack athletic activities compared to male students. Substantial changes were seen between the scores of anxiety (p<0.01), loneliness tendency (p<0.01), and phobia tendency (P<0.05) of high-scoring individuals in the game group before and after the experiment. According to the results, there was no significant difference between the game group and the non-game group with low scores in any indicator before and after the trial.